2018
DOI: 10.15294/kemas.v13i3.11092
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Areca Catechu L. Seed Extract on Mortality Anopheles Vagus Larvae

Abstract: Bioinsecticide is an alternative to overcome larva resistence to insecticide and reduce environtment contamination. This research is to analyze the effect of areca seed extract to An. vagus larva. The research is taken time in 2017. The research design is laboratory experiment with post test only control group design. The areca seed and An. vagus larva are collected from Kabupaten Sumba Barat Daya, then the seeds were extracted with ultrasonic method. The effect of the extract is evaluated based on LC50 and LC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
(5 reference statements)
0
2
0
2
Order By: Relevance
“…A previous study with A . catechu nut by Mading et al [ 35 ] showed that ethanol extraction with high concentrations showed mortalities in Anopheles vagus larvae. Similarly to recent studies by Ravindran [ 18 ] and Ravi et al [ 36 ], A .…”
Section: Discussionmentioning
confidence: 99%
“…A previous study with A . catechu nut by Mading et al [ 35 ] showed that ethanol extraction with high concentrations showed mortalities in Anopheles vagus larvae. Similarly to recent studies by Ravindran [ 18 ] and Ravi et al [ 36 ], A .…”
Section: Discussionmentioning
confidence: 99%
“…aqueous crude extract which is the first reported. The previous studies reported the medicinal use of betel nut with various properties, helminthicide, mosquito larvicidal, antimicrobial, anti-venom, and antioxidant (Ahuja and Ahuja, 2011;Jaiswal et al, 2011;Tennyson et al, 2012;Arulpriya et al, 2013;Sari et al, 2017;Sarpangala et al, 2017;Mading et al, 2018;Yamson et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Hal ini sesuai dengan peran ekstrak buah pinang muda (Areca catechu L.) yang mengandung senyawa polifenol, dimana senyawa golongan alkaloid, flavonoid dan tanin yang terdapat pada buah pinang, aktifitas dapat merusak sistem saraf larva dan memiliki aktivitas inhibisi enzim kolinesterase yang akan menyebabkan menurunnya koordinasi otot serta menghambat sistem pernapasan yang mengakibatkan kematian larva (Zulhar Riyaldi, 2018). Kandungan senyawa polifenol pada konsentrasi yang tinggi akan bersifat antifeedant bagi serangga, sehingga menyebabkan efek menurunkan aktivitas enzim pencernaan dan penyerapan makanan sehingga bersifat sebagai racun perut (Majematang Mading, 2018).…”
Section: Pembahasanunclassified